"Nothing Short of a Horror Show": Triggering Abjection of Street Workers in Western Canadian Newspapers. (19th December 2011) - Janzen, Caitlin; Strega, Susan; Brown, Leslie; Morgan, Jeannie; Carrière, Jeannine
<x xml:space="preserve">Abstract</x> Over the past decade, Canadian media coverage of street sex work has steadily increased. The majority of this interest pertains to graphic violence against street sex workers, most notably from Vancouver, British Columbia. In this article, the authors analyze newspaper coverage that appeared in western Canadian publications between 2006 and 2009. In theorizing the violence both depicted and perpetrated by newspapers, the authors propose an analytic framework capable of attending to the process of othering in all of its complexity. To this end, the authors supplement a Foucauldian analysis of abjection by considering the work of Judith Butler along with Julia Kristeva's conceptualization of abjection. Using excerpts from western Canadian newspapers, the authors illustrate how the media's discursive practices function as triggers for the process of cultural abjection by inscribing street sex workers with images of defilement. The authors argue that newspaper coverage of street sex workers reinforces the inviolability of normalized life by constantly reiterating the horror reserved for abjected bodies.